2020
DOI: 10.1111/dgd.12659
|View full text |Cite
|
Sign up to set email alerts
|

Polycomb group RING finger protein 5 influences several developmental signaling pathways during the in vitro differentiation of mouse embryonic stem cells

Abstract: Polycomb group (PcG) RING finger protein 5 (PCGF5) is a core component of the so‐called Polycomb repressive complex 1.5 (PRC1.5), which is involved in epigenetic transcriptional repression. To explore the developmental function of Pcgf5, we generated Pcgf5 knockout (Pcgf5−/−) mouse embryonic stem cell (mESC) lines with the help of CRISPR/Cas9 technology. We subjected the Pcgf5−/− and wild‐type (WT) mESCs to a differentiation protocol toward mesodermal‐cardiac cell types as aggregated embryoid bodies (EBs) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Importantly, in response to VPA, we also observed a significant increase in H3K56ac enrichment the TSS of Tnnt3 that overlapped with the observed ATAC-seq peak gain in the same genomic location, suggesting a coordinate transition toward a transcriptionally permissive chromatin environment. In addition, highly significant increases in chromatin accessibility at loci, such as alpha-T-catenin (Ctnn3) and polycomb group ring finger 5 (Pcgf5), further suggest that VPA exposure leads to changes in chromatin structure at specific key regulatory factors of cardiac and neuronal differentiation programs [ 43 , 44 ]. Intriguingly, loss of chromatin accessibility at putative downstream enhancer regions within the Hopx locus suggests that HOPX expression levels may be subjected to HDACi effects in mESCs.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, in response to VPA, we also observed a significant increase in H3K56ac enrichment the TSS of Tnnt3 that overlapped with the observed ATAC-seq peak gain in the same genomic location, suggesting a coordinate transition toward a transcriptionally permissive chromatin environment. In addition, highly significant increases in chromatin accessibility at loci, such as alpha-T-catenin (Ctnn3) and polycomb group ring finger 5 (Pcgf5), further suggest that VPA exposure leads to changes in chromatin structure at specific key regulatory factors of cardiac and neuronal differentiation programs [ 43 , 44 ]. Intriguingly, loss of chromatin accessibility at putative downstream enhancer regions within the Hopx locus suggests that HOPX expression levels may be subjected to HDACi effects in mESCs.…”
Section: Discussionmentioning
confidence: 99%
“…Neurodevelopmental processes are regulated by multiple factors that interact with various signaling pathways, including Notch, Wnt, Hedgehog, and TGF-β/BMP signaling pathways [ 37 ]. Pcgf5 is also involved in the regulation of multiple signaling pathways, such as the Notch and Wnt pathways [ 38 ]. It has been found that the loss of the Pcgf5 gene inhibits the expression of Notch1, thereby suppressing neural ectoderm differentiation [ 38 ], which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Pcgf5 is also involved in the regulation of multiple signaling pathways, such as the Notch and Wnt pathways [ 38 ]. It has been found that the loss of the Pcgf5 gene inhibits the expression of Notch1, thereby suppressing neural ectoderm differentiation [ 38 ], which is consistent with our findings. However, it is unclear whether there is an interaction and co-regulation between the Notch and Wnt signaling pathways in the process of neural development.…”
Section: Discussionmentioning
confidence: 99%
“…Several lincRNA-related loci were found to have altered methylation during memory activation in all three lineages, including LINC01258 locus to be demethylated in the memory lineages. LINC01258 is an ncRNA that targets the PCGF5 polycomb complex, which has a key role in differentiation and the NOTCH signaling pathway [ 56 ]. LINC01258 is upregulated in type 1 diabetes, a well-known immune disease [ 57 ].…”
Section: Discussionmentioning
confidence: 99%